Heuristics based on simulated annealing applied to the issue of berth allocation - Mauri, Geraldo Regis; Oliveira, Alexandre César Muniz de; Lorena, Luiz Antonio Nogueira (Revista Gestão da Produção Operações e Sistemas, 2008)
This work presents a Simulated Annealing based heuristic to solve the Berth Allocation Problem. This problemapproaches the programming and allocation of ships to mooring areas along a quay. The problem is modeled asa Multi-Depot Vehicle Routing Problem with Time Windows. The Simulated Annealing application uses threetypes of neighbors moves that are randomly selected. The computational results are obtained through tests problemsused in a recent work and compared against CPLEX and other method found in literature.Keywords: Berth Allocation Problem; Simulated Annealing; Vehicle Routing.